Analisis Keputusan Penggunaan QRIS Pada UMKM di Kelurahan Tanjung Duren Utara Dengan Perspektif Persepsi Kemudahan dan Persepsi Kegunaan Melalui Minat Sebagai Variabel Mediasi - Nasution, Ibnu Haris; Purnama, Yanthy Herawaty; R, Rahmat; Frimayasa, Agtovia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Digital transformation in payment systems has driven the adoption of the Quick Response Code Indonesian Standard (QRIS) as a more efficient transaction method for Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the influence of perceived usefulness and perceived ease of use on the decision to use QRIS, both directly and through interest as a mediating variable. The sample taken in this study was 97 MSME respondents. The research method used was Partial Least Squares - Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0, based on data collected from MSMEs in Tanjung Duren Utara Village. The results showed that perceived usefulness and perceived ease of use had a significant influence on the decision to use QRIS. In addition, interest proved to be a significant mediating variable, which strengthened the relationship between the two perception factors and the decision to use QRIS. The Q² value obtained showed that this research model had strong predictive ability, with the main contribution coming from perceived usefulness. This indicates that MSME actors are more likely to use QRIS if they feel that this technology provides real benefits in their business operations. Therefore, increasing QRIS adoption can be driven by educational and promotional strategies that emphasize the benefits and ease of use for MSMEs.